Transnational Higher Education and Sexual Harassment Policies: Kuwait - Fusilier, Marcelline (2021)
Transnational Higher Education and Sexual Harassment Policies: Kuwait Abstract Higher education is globalizing through transnational providers. While quality of educational services appears to receive considerable attention, the present study investigated whether workplace protection for employees in the form of sexual harassment prevention is similarly assured. The availability and characteristics of employee sexual harassment policies were compared across Kuwait for state, private for-profit, and foreign partner higher education organizations. Policies were collected from school web sites or by e-mailed and telephoned requests, and coded for their characteristics. The characteristics included such things as procedures for investigation of sexual harassment complaints, training for sexual harassment prevention, sanctions, etc. Results suggested that foreign partner higher education organizations appeared more likely to make policies available (70%) than colleges and universities based in Kuwait (33%). The foreign partner policies tended to have more characteristics than those based in Kuwait. Of the Kuwait schools that had policies, all were missing five of the 11 policy characteristics coded. Explanations for the findings and recommendations are discussed.